Reassignment of Improbable Natural Products Identified through Chemical Principle Screening. Issue 34 (13th July 2022) - Elyashberg, Mikhail; Novitskiy, Ivan M.; Bates, Roderick W.; Kutateladze, Andrei G.; Williams, Craig M.
Abstract: Natural products continue to be reported at an astonishing rate from a wide range of multidisciplinary research activities in the pursuit of understanding the chemistry of biodiversity. However, the elucidation of chemical structure in the modern era is heavily reliant on the analysis and interpretation of multiple spectroscopic outputs, and in most cases this activity is by no means trivial. Structural errors continue to be described given the inherent complexity of natural products. Computer‐Assisted Structure Elucidation (CASE) continues to provide improved resolving power in this regard, but for enhanced accuracy quantum chemical spectrum prediction methodology is paramount. Reported herein are a range of counterfactual natural products, identified through chemical principal screening, which have been reassigned using a combination of chemical intuition, chemical synthesis, CASE and DU8+ spectrum prediction. Abstract : Structure elucidation of complex natural products remains exceedingly reliant on a multitude of spectroscopic outputs, resulting in an elevated propensity to propose erroneous solutions. In this work concepts aimed to assist practitioners in identifying erroneous chemical structures are presented, along with nine examples to demonstrate approaches to solve and reassign natural product chemical structure employing a combination of CASE and DFT spectrum prediction with chemical intuition oversight.